A study on quality of life among thalassemic children aged 8 to 18 years - Jajhara, Indersain; Choudhary, Ganesh; Singh, Jagdish; Chachan, Vikal; Kumar, Anil (International Journal of Contemporary Pediatrics, 2021)
Background: The assessment of quality of life in children, especially in those with chronic illness such as thalassaemia, is particularly important. It differs from other forms of medical assessment in that it focuses on the individuals’ own views of their well-being and other aspects of life, giving a more holistic view of well-being. Methods: Hospital based descriptive, observational study was conducted on 200 school-age children. Two tools were used to collect the necessary data. The first was a structured interview questionnaire sheet including socio-demographic data of children and their parents as well as medical history. The second tool was a standardized tool (Pediatric Quality of Life Inventory TM Version 4.0). Results: The results of the present study revealed that the quality of life of school-age children with Thalassemia Major was affected. According to child’s report regarding total QOL score 30% of children had good score compared to 35% in parent’s report, while 65% had fair score compared to 60% in parent’s report. Emotional functioning scored the lowest followed by physical then school and social functioning. Regarding compliance with treatment, 91% of the studied children had regular blood transfusion therapy. In addition, 81% of the studied children were compliant with iron chelation therapy. Conclusions: Thalassemia has a negative impact on perceived physical, emotional, social and school functioning in thalassemia patients. There was a significant association between the total quality of life and compliance with blood transfusion and regular iron chelation therapy in both child and parent report.